Prevalence of Contraceptive Non-use Due to Husbands/Partners Influence Among Married Women in Ethiopia: A Multilevel Analysis Using Demographic and Health Survey 2016 Data - Asratie, Melaku Hunie; Kassie, Belayneh Ayanaw; Belay, Daniel Gashaneh (Frontiers in Reproductive Health, 2022)
Background In Ethiopia women with their husbands/partners are the decision-makers for contraceptives non-use suffered either due to the consequence of unintended pregnancy or due to the indirect impact of the secret use of contraceptives from their husbands/partners. Despite this challenge, there is a dearth of evidence about the magnitude of husbands/partners' decision-makers on contraceptives n non-used in Ethiopia. Objective This study was aimed to assess the magnitude of husbands'/partners decisions on contraceptive non-use and associated factors among married and non-contraceptive user reproductive-age women in Ethiopia. Methods The study was conducted based on Ethiopian demographic and health survey 2016 data which was a cross-sectional survey from 18 January 2016 to 27 June 2016. A total weighted sample size of 5,458 married and non-contraceptive user reproductive-age women were taken. A multilevel logistic regression model was used because of the data nature hierarchical, and variables with p ≤ 2 in the bivariable multilevel analysis were taken to multivariable multilevel analysis. Adjusted odds ratio with 95% CI was used to declare both the direction and strength of association and variables with p < 0.05 were considered statistically significant with the outcome variable. Results Husband decision-making power on contraceptive non-use was 10.44% [9.65–11.28%]. Husband's educational level higher (adjusted odds ratio (AOR = 2.6; CI 1.4–4.7), being Muslim, protestant, and others in religion (AOR = 2.4; CI 1.7–3.5), (AOR = 2.1; CI 1.4–3.1), (AOR = 4.5; CI 2.3–8.5), respectively, media exposure (AOR = 1.4; CI 1.0–1.8), husband wants more children (AOR = 3.7; CI 2.8–4.8), husband desire did not know (AOR = 1.4; CI 1.1–1.9), information about family planning (AOR = 0.6; CI 0.4–0.8), visited by field worker (AOR = 0.7; CI 0.5–0.9), visited health facility (AOR = 0.6; CI 0.4–0.7), and community husband education high (AOR = 1.6; CI 1.1–2.4) were statistically significant with husband decision making power on contraceptive non-use. Conclusion In Ethiopia 1 out of 10 married and non-pregnant women is influenced by their husband/partner's decision-making power of non-use contraceptives. Husband's educational level high, religion (Muslim, protestant, and others), media exposure, husband's desire for children (husband wants more and does not know), and community husband education were variables positively associated with the outcome variable; whereas having information about family planning, visited by field worker, and visited health facility were negatively associated husband decision making power for non-use contraceptive in Ethiopia.